Integration with the global economy. The case of Turkish automobile and consumer electronics industries - Erol Taymaz; Kamil Yilmaz (TÜSİAD-Koç University Economic Research Forum, 2008)
This paper aims to contribute to the extensive study of the World Bank Commission on Growth and Development by a case study of the Turkish automotive and the consumer electronics industries. Despite a macroeconomic environment that inhibits investment and growth, both industries have achieved remarkable output and productivity growth since the early 1990s and played a critical role in generating employment and fostering growth. Although there are similarities between the performances of automobile and consumer electronic industries, there seems to be significant differences between their structures, links with domestic suppliers, technological orientation and modes of integration with the global economy. The automobile industry is dominated by multinational companies, has a strong domestic supplier base, and has seized the opportunities opened up by the Customs Union by investing in new product and process technology and learning. The consumer electronics industry is dominated by a few, large domestic firms, and has become competitive in the European market thanks to its geographical proximity, productive domestic labor, and focus on a protected and technologically mature CRT color television receivers segment of the marker, which also helps explain the recent decline in industry's fortunes. It is without doubt that these industries could have performed even better had governments in Turkey adopted more responsive macroeconomic policies. It is certain that governments could be more responsive only if far-reaching political/institutional reforms are undertaken by changing the Constitution, and current political party and election laws in order to establish public control over the political elites.
Keywords: F14; L60; P16; 330; macroeconomic policies; automobile industry; consumer electronics industry; political elites; political reforms; Internationaler Wettbewerb; Wachstumsbranche; Wirtschaftspolitik; Kraftfahrzeugindustrie; Unterhaltungselektronische Industrie; Türkei